(untitled) (Research, Society and Development, 2021)
This study was aimed at estimating the prevalence of Common Mental Disorders (CMD) in graduates of Food Engineering and Civil Engineering at a public university in the northeast region of Brazil and to discuss the potential associated factors. Two questionnaires were used, one for specifically profiling the student, as well as the Self-Reporting Questionnaire (SRQ-20). The exploratory analysis of the data was carried out through descriptive statistics and through the calculation of simple and adjusted odd ratios. In the final adjusted model, independent variables correlated with the outcome after adjustment (p≤0.05) were maintained, considering the likelihood test, with 27.4% of the students who participated in the study (n = 161). The prevalence of CMD obtained for the population of this study was high (73.91%). The logistic regression analysis showed a strong association of individuals with CMD who do not work (RC = 3.240), who consider the course not as good as expected (RC = 2.682), whose performance was unsatisfactory (RC = 3.086) and who thought about giving up the course (RC = 3.613). These results reveal the need for discussion on this topic and the adoption of measures that can prevent the evolution of CMD in patients with major mental disorders, as well as seeking to understand what makes these students dissatisfied with their performance and with their teaching and learning strategies employed in these courses.